An Acoustofluidic Micromixer via Bubble Inception and Cavitation from Microchannel Sidewalls - Ozcelik, Adem (American Chemical Society, 2014)
[Image: see text] During the deep reactive ion etching process, the sidewalls of a silicon mold feature rough wavy structures, which can be transferred onto a polydimethylsiloxane (PDMS) microchannel through the soft lithography technique. In this article, we utilized the wavy structures of PDMS microchannel sidewalls to initiate and cavitate bubbles in the presence of acoustic waves. Through bubble cavitation, this acoustofluidic approach demonstrates fast, effective mixing in microfluidics. We characterized its performance by using viscous fluids such as poly(ethylene glycol) (PEG). When two PEG solutions with a resultant viscosity 54.9 times higher than that of water were used, the mixing efficiency was found to be 0.92, indicating excellent, homogeneous mixing. The acoustofluidic micromixer presented here has the advantages of simple fabrication, easy integration, and capability to mix high-viscosity fluids (Reynolds number: ∼0.01) in less than 100 ms.